PELATIHAN DESAIN PAMFLET MENGGUNAKAN APLIKASI CANVA BAGI SISWA JURUSAN TATA BOGA SMKN 4 BANJARMASIN - Fitria Fitria; Anhar Khalid (LPPM Universitas Bina Bangsa, 2024)
The Culinary Management Department is one of the leading majors that is in great demand by the public at SMKN 4 in the city of Banjarmasin. This department is also one of the outstanding departments because it often wins champions in School Skills Competitions (LKS) and actively participates in activities held by both the city government and national level, such as exhibitions and so on. Even though the Culinary Department is an outstanding department, there are several problems, including a lack of knowledge about the use of technology to support students in becoming entrepreneurs after graduating from school. When practicing designing with Canva, students are taught and guided to create a design, in this case a pamphlet for marketing tools or media for those who want to become entrepreneurs in the future